Pengaruh Iklan Digital, Influencer Marketing, Dan Content Marketing Terhadap Keputusan Pembelian Motor Trail Di Robby MX (Studi Kasus Pada Konsumen Di Robby MX ) - Mohammad Farkhan Isnani Al Ma’arif; Muhammad Ridwan Basalamah; Budi Wahono (E-JRM : Elektronik Jurnal Riset Manajemen, 2026)
Abstract This research examines how digital advertising, influencer marketing, and content marketing influence purchasing decisions among trail motorcycle consumers at Robby MX. A quantitative research design was applied through a survey approach. Primary data were obtained by distributing structured questionnaires to 80 Robby MX customers, with respondents selected using purposive and snowball sampling methods. The collected data were processed using multiple linear regression analysis after the measurement instruments were confirmed to be valid, reliable, and compliant with classical assumption requirements. The findings demonstrate that digital advertising, influencer marketing, and content marketing each exert a positive and statistically significant impact on consumer purchasing decisions, both individually and collectively. These results highlight the strategic role of digital-based marketing activities in shaping consumer decisions within the trail motorcycle market. Keywords:Digital Advertising, Influencer Marketing, Content Marketing, Purchasing Decision.